2021
DOI: 10.3390/cells10123506
|View full text |Cite
|
Sign up to set email alerts
|

The Stiffness of Cardiac Fibroblast Substrates Exerts a Regulatory Influence on Collagen Metabolism via α2β1 Integrin, FAK and Src Kinases

Abstract: Information about mechanical strain in the extracellular space is conducted along collagen fibers connected with integrins and then transmitted within cells. An aim of the study is to verify the hypothesis that the stiffness of cardiac human fibroblast substrates exerts a regulatory effect on collagen metabolism via integrin α2β1 and downstream signaling. The experiments were performed on human cardiac fibroblasts cultured on stiff or soft polyacrylamide gels. Extracellular and intracellular collagen content, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Next, we focused on exploring the molecular mechanisms by which the PFPF19/MYL9 axis promoted metastasis in CRC cells. Notably, previous studies have revealed that cytoskeletal tension and matric stiffness can activate the expression of Src [30][31][32], and actomyosin contractility and Src function are required for YAP1 activation by stiff matrices [19]. Moreover, high ECM stiffness could directly lead to nuclear localization and subsequent transcriptional activity of YAP1 [33,34], while actomyosin inhibition blocks the matrix remodeling and YAP1 activation, all of which implies that a functional contractile cytoskeleton is necessary for the activation of YAP1.…”
Section: Discussionmentioning
confidence: 98%
“…Next, we focused on exploring the molecular mechanisms by which the PFPF19/MYL9 axis promoted metastasis in CRC cells. Notably, previous studies have revealed that cytoskeletal tension and matric stiffness can activate the expression of Src [30][31][32], and actomyosin contractility and Src function are required for YAP1 activation by stiff matrices [19]. Moreover, high ECM stiffness could directly lead to nuclear localization and subsequent transcriptional activity of YAP1 [33,34], while actomyosin inhibition blocks the matrix remodeling and YAP1 activation, all of which implies that a functional contractile cytoskeleton is necessary for the activation of YAP1.…”
Section: Discussionmentioning
confidence: 98%
“…By transmitting mechanical cues into biochemical signals, cells respond through transcriptional regulation in the nucleus [ 93 , 105 ]. Gałdyszyńska M et al found α2β1 integrin and its downstream FAK/Src kinase signaling regulated collagen metabolism in cardiac fibroblasts cultured on the stiffer substrate, collagen content was elevated and regulated by MMP-1 and MMP-9 on soft substrates [ 106 ]. Yes-associated protein/transcriptional co-activator with PDZ-binding motifs (YAP/TAZ) are transcriptional co-activators that play a key role in the Hippo signaling pathway and are involved in various cellular processes.…”
Section: Mechanical Cues Regulate Fibroblasts By Various Signal Pathwaysmentioning
confidence: 99%
“…140 Moreover, scaffold stiffness regulates collagen metabolism in cardiac fibroblasts via integrin α2β1 and downstream signaling. 141…”
Section: Characteristics Of Scaffolds For Myocardial Repairmentioning
confidence: 99%
“…140 Moreover, scaffold stiffness regulates collagen metabolism in cardiac fibroblasts via integrin α2β1 and downstream signaling. 141 The viscoelasticity of hydrogels influences cell spreading, proliferation, migration and differentiation. In particular, cell spreading increased on elastic substrates, e.g.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%